Solution properties of mixed system containing butynediol-ethoxylate polysiloxanes and polyether trisiloxane surfactant - Zhang, Mi; Ning, Bo; Bai, Yanyun; Tai, Xiumei; Wang, Guoyong (Colloid and interface science communications, 2021)
To solve the problem of excess foam in an aqueous solution of polyether trisiloxane surfactant (PTS), butynediol-ethoxylate-modified polysiloxanes with different unit ratios (PSi-EOs; Pm-n = P2-8, P4-6, P5-5, P6-4) were introduced into the system, and properties of the PTS and PSi-EO mixture solutions were systematically studied. The interaction between them is elucidated by comparing the actual and ideal values of critical micelle concentration (cmc), maximum surface excess concentrations (Γmax), and minimum cross-sectional area (Amin). In addition, the interaction parameters and activity coefficients of the surfactant mixtures at the gas–liquid interface were determined. The mixed system has a high surface activity and wettability at the hydrophobic surface, similar to those of the individual PTS system, whereas the foam performance is significantly reduced for the mixed system. Moreover, foam stability of the mixed system deteriorates with a decrease in the hydrophilic group ratio in PSi-EO, and the formation mechanism of antifoaming is explained from the molecular perspective. Under the premise of hardly changing other physicochemical properties, PSi-EO has significant control effect on PTS low surface tension system. [Display omitted] •PSi-EO has a good control effect on the foam of polyether trisiloxane (PTS).•After the introduction of PSi-EO, the excellent surface activity and wettability of the system are almost not affected.•The less the number of hydrophilic groups introduced into PSi-EO, the worse the stability of the system foam.